Leveraging interest-growth differentials: Hidden effects of government financial assets in the European Union - Clarisse Wagner; José Alves (Journal of Economics, Finance and Administrative Science, 2025)
Purpose - Given that government financial assets represent a large proportion of gross debt accumulation, this study examines their impact on debt leveraging and potential returns on the gap between interest rates and economic growth (r-g). Design/methodology/approach - This research focuses on the co-movements of r-g differentials, government financial assets and the primary deficit through a channel of gross debt, investment, external balance and ratings, using a sample of 27 European Union economiesfrom2000 to 2022. The following co-integration methods were estimated: (1) for the aggregate, panel quantile autoregressive distributed lags (QARDL), ARDL- pooled mean group (PMG) for panel data, implemented with a (PMG) and (2) ARDL-error correction (EC) for individual countries at a granular level. Findings - While government financial assets drive short- and long-run debt trajectories, granular country heterogeneities reveal differentiated results for financial assets leveraging potential returns on the differential between interest rates and output growth (r-g). Government financial assets may enhance r-g, but may risk even undermining gainsfrom primary deficit consolidation efforts. By comparing aggregate estimations with country granular approaches, outliers from non-statistically significant estimations reveal the epistemological limits of aggregation, statistics and probability theory, warning against overconfidence in such mere guidance tools, which are not safeguarding guarantees. Research limitations/implications - Statistical asymptotics and instability of non-independent and identical distributions may underestimate variance. Furthermore, skewness and leptokurtosis may benefit from extreme value theory. In addition, technological changes, policy regimes, geopolitical events and economic crises can change in-built long-run relationships. Practical implications - Heterogeneity of governmentfinancial assets effects depend on socio and macrofinance conditions, advocating the principle of subsidiarity. Financial assets, such as sovereign wealth funds linked to naturalresources, oil in Norway, copperinChile,may benefitfromfinancial assets assessments.The strengthening of democratic accountability calls for transparency about financial assets contribution to debt trajectories, r-g effects and risks of potential undermining primary deficit consolidations. Accounting reporting should appropriately disclose changes in assets value from exposition to market volatility, accumulation of holding costs due to constraints to asset liquidation, due to non-active secondary markets, or long investment horizons. Social implications - To strengthen democratic accountability, there should be transparency about their contribution to debt trajectories, r-g effects and risks to potential undermining primary deficit consolidation. Their performance depends on financial markets and socio- and macro-finance conditions, calling for the principle of subsidiarity. Originality/value - Rather than the traditional emphasis on government debt, this study examines the leverage effect on the gap between interest rates and economic growth (r-g differential). While the literature primarily addresses stock-flow adjustments (SFAs), the focus is narrowed to financial assets underlying government interventions on the supply side of the economy. Evidence is provided on the risks of financial assets undermining primary deficit consolidation efforts. While the literature highlights the short and medium terms, estimates are divided into short-term dynamics and hypothetical in-built long-run cointegrations. Panel aggregation is compared with granular estimates, uncovering heterogeneities and supporting governance subsidiarity. Support for statistical pluralism is provided by comparing results and methodological limitations.
Keywords: C23; E44; F65; H60; H63; 330; Public debt; Financial assets; QARDL; ARDL; PMG